Production optimization for sustainable agriculture and efficient contract farming in the Republic of Maldives - Abdulla, Nadhiya; Абдулла, Надія; Vasylieva, Natalia; Васильєва, Наталя Костянтинівна; Volovyk, Iryna; Воловик, Ірина Анатоліївна (Сільськогосподарська академія Болгарії, 2022)
This research study is carried out to identify the efficiency of farms in crop production from three different regions of Maldives, which have started the contracting farming in 2021 to improve their sustainability and farm management. The research question concerns about crop efficiency evaluation, to identify how the production of crops can be distributed among 3 regions of Maldives to optimize farming under conditions of soil limits and climate changes. A total of 13 islands were visited and data from 700 farmers were collected. In addition to this, more than 1200 farmers were directly intervened to understand the nature of their farming and understanding the situation of agriculture in the Maldives. Atolls were divided into 3 major regions and data were analyzed using tool Solver built in the spreadsheet MS Excel. It shows that region 3 can reduce its input cost by 7%, and in region 2 by 43% by incorporating these criterions. It also suggests that following these criterions it would increase total farmers income by 59% about its initial value, thus enhancing Maldivian food security and improving welfare of the local farmers. The study reveals that different regions must focus on certain area related crops and should redistribute and relocate land area for specific crops to decrease production expenditures. Це дослідження проводиться з метою виявлення ефективності господарств у рослинництві з трьох різних регіонів Мальти. dives, які розпочали контрактне фермерство у 2021 році, щоб покращити свою стійкість та управління фермою. Дослідження поставити питання про оцінку ефективності сільськогосподарських культур, щоб визначити, як виробництво сільськогосподарських культур можна розподілити між 3 регіонами Мальдівських островів для оптимізації землеробства в умовах обмеженості ґрунту та зміни клімату.
Оптимізація виробництва для сталого сільського господарства та ефективного контрактного фермерства в Республіці Мальдіви
Keywords: сontract farming; контрактне фермерство; resource management; управління ресурсами; optimization model; модель оптимізації; regional agriculture; регіональне сільське господарство